An Immersive Journey Through Early Electronic Works of… Luigi Nono - Parra Cancino, Juan; An Immersive Journey Through Early Electronic Works of… Luigi Nono Koetshuis Orpheus Instituut January 29, 2024 (2024)
Tape, Vinyl, and digital, multichannel fixed support pieces, presented in their original formats.
Listening sessions of Early Electronic Music
FRIS
0
Keywords: Music, Thought and Technology